An experimental study of the torque-tension relationship for bolted joints. (1st January 2001) - Jiang, Yanyao; Chang, Jianjun; Lee, Chu-Hwa
An experimental approach to determining the torque-tension relationship for a typically used bolted joint was developed. In addition to the bulk torque-tension relationship, the experiments measured the thread friction and the bearing friction between the nut surface and the clamped surface. The influence of the use of washers made of different materials under repeated tightening was studied. A statistics analysis was conducted to allow for a reliability assessment of the bolted joints in terms of the clamping force control.